2021
DOI: 10.3325/cmj.2021.62.387
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating comorbidities and predicting prognosis in idiopathic normal pressure hydrocephalus using cerebrospinal fluid biomarkers

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) is a condition resulting from impaired cerebrospinal fluid (CSF) absorption and excretion characterized by a triad of symptoms comprising dementia, gait disturbance (impaired trunk balance), and urinary incontinence. CSF biomarkers not only assist in diagnosis but are also important for analyzing the pathology and understanding appropriate treatment indications. As the neuropathological findings characteristic of iNPH have yet to be defined, there remains no meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 63 publications
0
4
0
10
Order By: Relevance
“…Für gewöhnlich profitieren Patienten mit iNPH insbesondere hinsichtlich Gangstörung und Inkontinenz, kognitive Defizite scheinen weniger gut modulierbar [4]. Bislang existiert kein Instrument, mit dem ein iNPH mit 100 %iger Sensitivität und Spezifität diagnostiziert werden könnte [13]. Eine VP-Shuntversorgung sollte bei typischer Klinik, hinweisendem Bildbefund und Ansprechen auf Liquorablass angeboten werden [12].…”
Section: Bildgebungunclassified
See 2 more Smart Citations
“…Für gewöhnlich profitieren Patienten mit iNPH insbesondere hinsichtlich Gangstörung und Inkontinenz, kognitive Defizite scheinen weniger gut modulierbar [4]. Bislang existiert kein Instrument, mit dem ein iNPH mit 100 %iger Sensitivität und Spezifität diagnostiziert werden könnte [13]. Eine VP-Shuntversorgung sollte bei typischer Klinik, hinweisendem Bildbefund und Ansprechen auf Liquorablass angeboten werden [12].…”
Section: Bildgebungunclassified
“…Da eine Ventrikelerweiterung im höheren Lebensalter häufig ist, sollte der Grad der kortikalen Atrophie in Relation zur Ventrikelerweiterung eingeschätzt werden [12]. Ein Missverhältnis von Seitenventrikelerweiterung und vertexnah engem oder verstrichenem Kortexrelief wird als DESH (disproportionately enlarged subarachnoid space hydrocephalus) bezeichnet [13], was aus diagnostischer Sicht einem qualitativen Kriterium entspricht Eine Alternative zum Liquorablassversuch ist die lumbale Drainage mit einer Drainagerate von 5-10 ml/Stunde über einen Zeitraum von 2-7 Tagen. In kleineren Fallserien wies sie eine Spezifität und Sensitivität von 100 % für das Ansprechen auf die VP-Shuntversorgung auf [32].…”
Section: Bildgebungunclassified
See 1 more Smart Citation
“…In modern studies, around 80% of treated patients experience improved symptoms [ 2 ]. In spite of extensive research into a wide range of radiological [ 3 , 4 ], biochemical [ 5 ] and hydrodynamic [ 6 8 ] markers, to date no specific test can adequately diagnose iNPH or predict which patients will benefit from shunt surgery. Reliable tests for the prediction of outcomes are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…A potentially useful method is to provide quantitative CSF samples during aspiration tests (de Laurentis et al, 2020 ). Although there are no extremely sensitive and specific CSF biomarkers that may predict the efficacy of a CSF shunt intervention, several studies have shown the potential of A42, p-tau, total tau, NfL, and LRG (Nakajima et al, 2021 ; Thavarajasingam et al, 2022 ). Additionally, AQPs may be used as therapeutic targets (Rizwan Siddiqui et al, 2018 ; Ding et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%